CUSTOMARY DELIBERATION IN CONTEMPORARY ISLAMIC LAW: EXAMINING THE IMPLEMENTATION SYSTEM OF WEST MALALAK KENAGARIAN IN INDONESIAN FIKIH AND SIYASAH DUSTURIYAH - Arianto, Ferdian; Saebani, Beni Ahmad; Sutiana, Yana (Universitas Islam Indonesia, 2025)
Purpose - This research analyzes the Nagari system of governance in West Sumatra as an independent customary law system rooted in family and blood relations. In addition, it examines the respect for this system in its day, including by the Dutch colonial government, and its impact on modern regulation. Contemporary Islamic law is also examined in supporting or criticizing this system, particularly concerning justice, deliberation, and leadership. Methods - This research uses a qualitative method with an empirical juridical approach and descriptive analysis. Data were collected through direct observation and recording of social and legal phenomena in Nagari communities. Findings - The results showed that West Sumatra is a village-based customary law society with a unique organizational structure now regulated in Law No. 6 of 2014. The democratic system of the Minangkabau Nagari Community has the disadvantage of being hereditary, which can inhibit more inclusive leadership dynamics. Its political structure tends to be paternalistic, influencing patterns of governance and decision-making. Contribution/Limitation - This research helps to understand the dynamics of the Nagari government system in the context of customary law and the challenges of modernization. In addition, it examines the relevance of this system to contemporary Islamic legal principles, particularly in social justice, leadership transparency, and community participation. However, this research is limited to analysis in West Sumatra and does not include comparisons with other regions. Originality/Value - This research provides insight into the sustainability of the Nagari government system in the face of modern regulations and social dynamics, as well as its relevance in contemporary Islamic law.